Purchasing house preferences among person with disabilities (PWD) in Kuala Lumpur - Ab Rahman, Syakir Amir (IIUM Press, 2019)
In Malaysia, disabled people have often been ignored and manipulated especially on their rights and full participation within community. Being aware of this scenario, the Department of Social Welfare Malaysia as one of the responsible government agencies has always implemented programs and strategies in protecting this vulnerable group. Therefore, this paper identifies the preferences in purchasing a house in accordance to the type of disabilities which are visually impaired and physically challenged people on the related issues in terms of design, price and location of a house. A total of 400 respondents in Kuala Lumpur were involved in the questionnaire survey. It was found that about 60.5% respondents have a priority in choosing a desirable location as the key principle in purchasing a house which constitutes for a safe neighbourhood and proximity to working place, service and facilities. Overall, housing provision for disabled people should afford the same standard of comfort, choice and accessibility. Hence, further research is needed to determine the appropriate criteria that encourage independent living which suit their capability and satisfy their needs.